Mapping PT PLN (Persero) Consumer Willingness to Make Electricity Account Payments (Willingness To Pay) Based on Regional Characteristics Using the Ranking Analysis Method - Rahmada Mulia Whardana Moljoadie (International Journal of Social Service and Research, 2023)
Like companies that are oriented to the buying and selling business in general, PT PLN (Persero) or PLN also has the same business risk, namely the existence of accounts receivables arising from electricity buying and selling transactions with consumers. By getting cash in from billing electricity bills, PLN's operations will of course be maintained so that service to customers can be even better. To support securing the company's cash flow, it is necessary to carry out an analysis related to external factors that influence the willingness to pay electricity bills by looking at the characteristics of regional conditions so that mitigation can be carried out to control electricity receivables. One of the relevant methods to obtain a mapping of consumers' willingness to make electricity bill payments is to use the ranking analysis method, which is an analysis of several rankings on methods including conducting surveys, interviews with experts based on the Delphi method ( 2 rounds of interviews) and statistical calculations using the independent sample t-test and the final test using the Borda calculation method. In this study, the factors that most influenced customer behavior related to their willingness to pay electricity bills were obtained based on regional characteristics, namely regional education and culture factors, economic factors and consumer income then the electricity service reliability factor. The mapping of these factors can be used by companies as one of the considerations for making decisions to develop operational strategies in an effort to control the values of electricity account receivables.